A Moral Imperative: Retaining Women of Color in Science Education - Johnson, Angela; Anderson, Sybol Cook; Norlock, Kathryn (Atlantis, 2009)
This article considers the experiences of a group of women science students of color who reported encountering moral injustices, including misrecognition, lack of peer support, and disregard for their altruistic motives. We contend that university science departments face a moral imperative to cultivate equal relationships and the altruistic power of science.